2007
DOI: 10.1617/s11527-007-9268-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of demoulding mechanisms at the formwork/oil/concrete interface

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 5 publications
4
29
0
3
Order By: Relevance
“…It can be observed that the friction stress decreases in the presence of the oils, and especially of the vegetablebased oil, which confirms the findings in Libessart's dissertation [6]. A new boundary layer comprising water, fines and oil is created.…”
Section: Influence Of the Nature Of Release Agentssupporting
confidence: 84%
See 1 more Smart Citation
“…It can be observed that the friction stress decreases in the presence of the oils, and especially of the vegetablebased oil, which confirms the findings in Libessart's dissertation [6]. A new boundary layer comprising water, fines and oil is created.…”
Section: Influence Of the Nature Of Release Agentssupporting
confidence: 84%
“…In this case, the thickness of the oil film is an important parameter [6,7]. The thicker the film, the less aggregate comes into contact with the plate.…”
Section: Influence Of the Nature Of Release Agentsmentioning
confidence: 99%
“…Although a few muralist precursors raised the question of mortar aesthetic at the beginning of the 20th century [1][2][3][4], it only became a major concern in the last decades [4][5][6][7][8][9][10]. The development of high-performance and self-compacting concretes [11][12][13][14], which show a significant improvement in terms of aesthetics, contributed to develop their use in architecture.…”
Section: Introductionmentioning
confidence: 99%
“…These agents reduce adhesion and friction between the concrete and the formwork. As a result, the quality of the product is enhanced and the life of the formwork is extended [11,12]. The most common commercial release agents for concrete are paraffinic and naphthenic derivatives obtained by the distillation of petroleum and frequently improved with chemical additives such as organic acids or modified esters.…”
Section: Introductionmentioning
confidence: 99%
“…The project, ''Substitution of Mineral Oil based concrete mold release agents by non-toxic, readily biodegradable, Vegetable oil based Release Agents'' [33], was undertaken by the European Union, resulting in guidelines on the use of biodegradable release agents as well as tests necessary to evaluate their performance. A substantial amount of research on biodegradable emulsions reported the successful use of rapeseed or soybean oil as a base for the formulations [10][11][12][13][14]17]. However, there is no scientific explanation related to the role of the chemical composition in release agent performance in steel-concrete interfaces.…”
Section: Introductionmentioning
confidence: 99%